Energy storage and attrition performance of limestone under fluidization during CaO/CaCO3 cycles. (15th September 2020) - Ma, Zhangke; Li, Yingjie; Zhang, Wan; Wang, Yuzhuo; Zhao, Jianli; Wang, Zeyan
Abstract: Thermochemical energy storage of CaO/CaCO3 system is a rapidly growing technology for application in concentrated solar power plant. In this work, the energy storage reactivity and attrition performance of the limestone during the energy storage cycles were investigated in a fluidized bed reactor. The effects of CO2 concentration, reaction temperature, fluidization velocity, particle size and number of cycles were discussed. With increasing CO2 concentration from 80% to 100%, the energy storage capacity and attrition rate of the limestone increase by 11% and 9%, respectively. The feasible carbonation and calcination temperatures are 850–870 °C and 800–850 °C, respectively. The energy storage capacity of the limestone improves with increasing fluidization velocity in carbonation stage. As the fluidization velocity increases from 0.04 to 0.06 m/s, the attrition rate of the limestone after 5 cycles increases by 96%. Smaller particles show higher energy storage and attrition resistance during the cycles. Further, the cyclic stability of the limestone carbonated at higher fluidization velocity is higher than that carbonated at static (solid-like) state. The limestone operated at the fluidization state exhibits a higher cyclic energy storage capacity than that at the static (solid-like) state. Higher fluidization velocity significantly mitigates the pore-plugging and sintering of the limestone. Highlights: Energy storage and attrition behaviors of limestone are studied in a fluidized bed. Limestone achieves high cyclic energy storage capacity under fluidization. Limestone presents a good attrition resistance in energy storage under fluidization. High fluidization velocity mitigates pore-plugging of limestone for energy storage.